What the worker should know - Ryan, Frederick W. (Statistical and Social Inquiry Society of Ireland, 1923)
A belief in the extension of education for the multitude in new ways and in subjects hitherto untouched by the masses is manifest. Three important schemes are in operation.
Read April 7, 1921
Keywords: Adult education; Literacy; 314.15